Partisipasi Orang Kristen dalam Membangun Toleransi Beragama di Indonesia: Integrasi Atas Sila Pertama Pancasila dan 1 Korintus 9:20-22 - Simanjuntak, Harlinton; Gea, Meylinda; Sumakul, Benaya Matthew Waraney (STT Internasional Harvest Tangerang, 2025)
Several research reports indicate that cases of religious intolerance are still rampant in Indonesia. To address this challenge, collective awareness is needed to foster a spirit of religious tolerance. Pancasila and the Bible provide philosophical, political, and practical foundations for realizing the spirit of tolerance, particularly the first principle of Pancasila and 1 Corinthians 9:20-22. This research was conducted using a literature study method with an interpretive-integrative approach, namely an interdisciplinary study, particularly through the perspectives of Pancasila and the Bible. The results of the study show that there are three interrelated dimensions: the practical dimension, the philosophical dimension, and the political dimension. In principle, the first principle of Pancasila emphasizes the significance of recognizing plurality and religious freedom in Indonesia. On the other hand, 1 Corinthians 9:20-22 provides a biblical spirit that encourages the creation of adaptive interactions within a pluralistic society. Thus, the integration of Pancasila and the Bible in this study opens up the horizon of interdisciplinary knowledge in academic research and can strengthen the principles that can build a spirit of religious tolerance in Indonesia through interdisciplinary studies